2016
DOI: 10.1111/mam.12069
|View full text |Cite
|
Sign up to set email alerts
|

Mysticete migration revisited: are Mediterranean fin whales an anomaly?

Abstract: 1.The generally accepted model of Mysticete whale migration is that most individuals undertake seasonal migrations between high and low latitudes. Although numerous exceptions have been described in the literature, the traditional model remains unexamined. This paper represents the first 'official' challenge to the traditional model of Mysticete migration. 2. We set out to review the current state of knowledge on the Mediterranean fin whale migratory pattern, and to examine whether the small, resident populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 82 publications
(145 reference statements)
5
92
0
Order By: Relevance
“…Reilly & Thayer 1990, Mate et al 1999, Visser et al 2011, Silva et al 2013, Owen et al 2015. A closer look at seasonal movements within and across baleen whale populations has revealed that dynamic migration strategies do not conform with a feast and famine yearly cycle (Geijer et al 2016). For instance, blue whales in the northeastern Pacific exhibit ARS behaviour throughout the migratory cycle (Bailey et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reilly & Thayer 1990, Mate et al 1999, Visser et al 2011, Silva et al 2013, Owen et al 2015. A closer look at seasonal movements within and across baleen whale populations has revealed that dynamic migration strategies do not conform with a feast and famine yearly cycle (Geijer et al 2016). For instance, blue whales in the northeastern Pacific exhibit ARS behaviour throughout the migratory cycle (Bailey et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These include several areas along the slope of the Laurentian Channel, the continental shelf edge, and sectors within shelf habitats (depth <100 m) of the SLE and GSL (Simard & Lavoie 1999, Lavoie et al 2000, Sourisseau et al 2006, Plourde et al 2016. The classical depiction of the annual cycle of capital breeding mysticetes involves alternating feast and famine as the animals move from their feeding to breeding areas (Lockyer & Brown 1981, Clapham 1996; although see exceptions in Geijer et al 2016). However, migrating animals likely encounter zones of heightened productivity in the open ocean, where intermittent feeding may occur during winter and spring (Silva et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations